(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe infant and young child feeding (IYCF) practices among children aged 0–23 months and analyze associated factors in Hanoi, Vietnam. Methods: A cross-sectional study was conducted with 1,195 children and their mothers. Data were collected via direct interviews and anthropometric measurements. IYCF indicators included exclusive breastfeeding (EBF), minimum dietary diversity (MDD), minimum acceptable diet (MAD), and underweight status (Weight-for-Age Z-score – WAZ < −2SD). Univariable and multivariable logistic regression analyses were performed to examine the associations between IYCF practices and potential factors. Results: The prevalence of EBF among children aged 0–5 months was 41.5%, and 69.4% of children were given bottle feeding. Among children aged 6–23 months, 67.2% achieved MDD and 44.8% achieved MAD. Infants aged 0-5 months who are bottle-fed are only 0.12 times more likely to be exclusively breastfed compared to infants who are not bottle-fed (OR=0.12; 95% CI: 0.07-0.21; p<0.001). Children aged 6–23 months who achieved MAD had 2.02 times higher odds of being underweight than those not achieving MAD (OR = 2.02; 95% CI: 1.01–4.07; p = 0.047), reflecting reverse causality. Maternal education and residential area were also associated with IYCF practices. Conclusions: Infant and young child feeding practices in Hanoi reflect diverse caregiving behaviors. Efforts are needed to educate parents, promote exclusive breastfeeding, reduce bottle feeding, and improve complementary feeding quality, along with regular monitoring of child growth to enhance nutritional outcomes.